Implementing nursing round to deal with unresolved nursing problem on patient with acute pain: A case report - Ike Nesdia Rahmawati (SAGE Publishing, 2021)
Background: The determining factors for improvement of health services quality includes nursing services. Furthermore, a method for providing this quality nursing services is professional nursing care model, and comprises nursing round. However, fewer hospitals implement this due to several barriers including lack of knowledge and practices. This study is, therefore, aimed at identifying improvements in quality of nursing care and solving of patient's problem by frequent nursing rounds. Design and Method: This study employed a single case report design using exploratory and descriptive methods. A 27-year-old male underwent nephrectomy surgery to treat hydronephrosis. The person still revealed persistent pain in the surgery area even though it has been treated for 3 days. The staff nurses administered nursing round to discuss and solve this problem. The study participation was voluntary, while the involved patient gave the informed consent. The steps of nursing round procedure including preround, round, and post-round were used to solve the problem. Results: The results indicated that nurses discovered blood clots in the patient's drain during nursing round. The cause of the persistent pain was revealed and used to determine the intervention modification needed. It was recommended to evacuate the blood clot and followed by appropriate pain management. Furthermore, the problem in the patient with acute pain was resolved. Conclusions: This study reveals the effectiveness of regular nursing rounds to enhance the outcome of nursing care and indirectly shows an increase in quality of nursing services provided. Therefore, to optimize nursing rounds, the commitment of the nursing management is significant.